Pillararene‐Based Two‐Component Thixotropic Supramolecular Organogels: Complementarity and Multivalency as Prominent Motifs. Issue 59 (19th September 2018) - Zafrani, Yossi; Kaizerman, Dana; Hadar, Maya; Bigan, Nitzan; Granot, Eran; Ghosh, Moumita; Adler‐Abramovich, Lihi; Patolsky, Fernando; Cohen, Yoram
Abstract: Invited for the cover of this issue is the group of Yossi Zafrani and Yoram Cohen at the Tel Aviv University. The image depicts an artistic rendition of the supramolecular organogel with nanotubular molecular core structure. Read the full text of the article at 10.1002/chem.201801418 . Abstract : " The present study describes a rationally designed thixotropic two‐component supramolecular organogels based on multiple chemical interactions between percarboxylato‐ and peramino‐pillar[5]arenes ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 15750 ff. (DOI: 10.1002/chem.201801418 ).